Entrepreneurial Marketing from the Perspective of Strategic Innovation - Simona-Valentina Pașcalau (Agora International Journal of Economical Sciences (AIJES), 2018)
The purpose of this paper is to identify the implications of strategic innovation in entrepreneurial marketing. This article aims to define and analyze concepts such as: entrepreneurship, entrepreneurial marketing, innovation, innovation management. We will also present the priorities in the reconceptualization of marketing, we will discover the approach of strategic innovation, strategic thinking in marketing and the issue of strategic thinking.
Keywords: 330